1993
DOI: 10.1007/bf00024843
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth regulators and the orchid cut-flower industry

Abstract: Research involving plant growth regulators (PGRs) and orchids in areas of orchid growth and development are reviewed . For all areas covered in the review -seed germination and seedling growth, lateral shoot production, root production, flower initiation and development, postharvest physiology, and photosynthate partitioning -it was concluded that further studies would assist in clarifying potential uses for PGRs in the orchid cut-flower industry . It is suggested that extra PGR research on orchids is justifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…However, in some orchid nurseries, floral bud drop has become a big problem affecting quality and commercial value of the plants. Numerous studies have reported floral bud drop in popular tropical orchids grown for cut flowers, and consequently, many farmers in South-East Asia have stopped growing Aranthera Beatnice Eng and Dendrobium Sri Siam because of this bud drop problem (Hew and Clifford 1993). Less information is available on bud drop in miniature orchids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some orchid nurseries, floral bud drop has become a big problem affecting quality and commercial value of the plants. Numerous studies have reported floral bud drop in popular tropical orchids grown for cut flowers, and consequently, many farmers in South-East Asia have stopped growing Aranthera Beatnice Eng and Dendrobium Sri Siam because of this bud drop problem (Hew and Clifford 1993). Less information is available on bud drop in miniature orchids.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that floral buds of various orchids are sensitive to ethylene (Hew and Clifford 1993). In Dendrobium, it has been observed that abscission of floral buds and flowers took place frequently during transportation in sealed cardboard boxes.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene has a regulatory effect, at the transcriptional and the translational level, on expressed genes that are involved in organ abscission-related cell separation (Brown 1997). Bud and flower drop in orchids during transportation and dark storage is a serious problem, consequently, many farmers in South-East Asia have stopped growing Aranthera 'Beatnice Eng' and Dendrobium 'Sri Siam' because of this bud drop problem (Hew and Clifford 1993).…”
Section: Ethylene Insensitivity Delays Flower Senescence and Inhibitsmentioning
confidence: 99%
“…Numerous studies have reported ethylene-induced floral bud drop and floral senescence in different orchids grown for cut flowers or as potted plants (Hew and Clifford 1993;Rattanawisalanon and others 2003;Huang and Paull 2009;Sun and others 2009;Raffeiner and others 2009b).…”
Section: Introductionmentioning
confidence: 96%
“…Little is known about assimilate partitioning in orchids despite the value of such information for improved flower production in those hybrids grown for the international cut-flower market (Hew & Clifford, 1993), Our recent studies have shown that *To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%